Pengaruh Gaya Hidup Hedonisme dan Kontrol Diri Terhadap Perilaku Konsumtif Pada Guru Di Sekolah Menengah Kejuruan Negeri Kabupaten Gowa - Karnedy, Astari; Thalib, Syamsul Bachri; Nur, Haerani (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Teachers at vocational high schools (SMK) in Gowa Regency are professional educators who serve as role models for students and play a vital role in enhancing the quality of human resources through education. This quantitative study aims to examine the influence of a hedonistic lifestyle and self-control on consumptive behavior among teachers at public vocational high schools in Gowa Regency. A total of 172 teachers participated in the study. Data were collected using three scales: a hedonistic lifestyle scale, a self-control scale, and a consumptive behavior scale. The results indicate a positive and significant influence of a hedonistic lifestyle on consumptive behavior (r = 0.485, p = 0.000), a negative and significant influence of self-control on consumptive behavior (r = -0.516, p = 0.000), and a combined positive and significant influence of both variables on consumptive behavior (r = 0.815, p = 0.000). These findings suggest that while a hedonistic lifestyle tends to increase consumptive behavior, higher self-control can reduce it. Therefore, both variables significantly contribute to shaping the consumptive behavior of vocational high school teachers in Gowa Regency